Reductive amination with zinc powder in aqueous media - Giovenzana, Giovanni B.; Imperio, Daniela; Penoni, Andrea; Palmisano, Giovanni (Beilstein Journal of Organic Chemistry, 2011)
Zinc powder in aqueous alkaline media was employed to perform reductive amination of aldehydes with primary amines. The corresponding secondary amines were obtained in good yields along with minor amounts of hydrodimerization byproducts. The protocol is a green alternative to the use of complex hydrides in chlorinated or highly flammable solvents.
Keywords: aldehydes; amines; reductive amination; water; zinc